Insights on the neural basis of motor plasticity induced by theta burst stimulation from TMS–EEG. Issue 4 (28th November 2012) - Vernet, Marine; Bashir, Shahid; Yoo, Woo‐Kyoung; Perez, Jennifer M.; Najib, Umer; Pascual‐Leone, Alvaro
Abstract Transcranial magnetic stimulation (TMS) is a useful tool to induce and measure plasticity in the human brain. However, the cortical effects are generally indirectly evaluated with motor‐evoked potentials (MEPs) reflective of modulation of cortico‐spinal excitability. In this study, we aim to provide direct measures of cortical plasticity by combining TMS with electroencephalography (EEG). Continuous theta‐burst stimulation (cTBS) was applied over the primary motor cortex (M1) of young healthy adults, and we measured modulation of (i) MEPs, (ii) TMS‐induced EEG evoked potentials (TEPs), (iii) TMS‐induced EEG synchronization and (iv) eyes‐closed resting EEG. Our results show the expected cTBS‐induced decrease in MEP size, which we found to be paralleled by a modulation of a combination of TEPs. Furthermore, we found that cTBS increased the power in the theta band of eyes‐closed resting EEG, whereas it decreased single‐pulse TMS‐induced power in the theta and alpha bands. In addition, cTBS decreased the power in the beta band of eyes‐closed resting EEG, whereas it increased single‐pulse TMS‐induced power in the beta band. We suggest that cTBS acts by modulating the phase alignment between already active oscillators; it synchronizes low‐frequency (theta and/or alpha) oscillators and desynchronizes high‐frequency (beta) oscillators. These results provide novel insight into the cortical effects of cTBS and could be useful for exploring cTBS‐induced plasticity outside of the motor cortex.